STRATEGI DINAS KEBUDAYAAN DAN PARIWISATA DALAM KONTRIBUSI PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN BOJONEGORO - Noveliadi, Angel Vishinta Putri (Universitas 17 Agustus 1945 Surabaya, 2017)
Culture and Tourism Service Strategy in the Contributation of Local Revenue Increase in Bojonegoro. Tourism that can be packaged and managed properly will be an asset for an area. The diversity of tourist attraction in Bojonegoro Regency can actually be used as one of the economic supporters and also can absorb a lot of manpower so that human resources and natural resources can be utilized optimally. The purpose of this study is to determine the strategy of the Department of Culture and Tourism in the Contribution of Income Revenue Original. This research uses descriptive qualitative research method by using informant from Department of Culture and Tourism of Bojonegoro Regency. The results of research are aspects affecting tourism in Bojonegoro regency. Analysis of the internal and external environment of the organization aims to find out the strategic issues of the Department of Culture and Tourism of Bojonegoro Regency using SWOT analysis (Strenghts, Weaknes, Opportunities, Threats). Â Keywords: Strategy, Tourism, Local Original Income, SWOT Analysis